Adapting and piloting a social contact-based intervention to reduce mental health stigma among primary care providers: Protocol for a multi-site feasibility study - Dristy Gurung; Brandon A. Kohrt; Syed Shabab Wahid; Kalpana Bhattarai; Binita Acharya; Feryel Askri; Bethel Ayele; Ioannis Bakolis; Anish Cherian; Mercian Daniel; Kamal Gautam; Eshetu Girma; et al. (Elsevier, 2023)
Stigma among primary care providers (PCPs) is a barrier to successful integration of mental health services in primary healthcare settings globally. Therefore, cross-culturally adaptable and feasible strategies are needed to reduce stigma among PCPs. This protocol is for a multi-site pilot study that aims to adapt and evaluate cross-cultural feasibility and acceptability of a social contact-based primary healthcare intervention in 7 sites in 5 low-and-middle-income countries. A mixed methods pilot study using an uncontrolled before-after study design will be conducted in China (Beijing, Guangzhou), Ethiopia (Sodo), India (Bengaluru, Delhi), Nepal (Syangja), and Tunisia (Testour). The intervention, entitled REducing Stigma among HealthcAre ProvidErs (RESHAPE), is a collaboration with people with lived experience of mental health conditions (PWLE), their family members, and aspirational figures (who are PCPs who have demonstrated high motivation to integrate mental health services). PWLE and their family members are trained in a participatory technique, PhotoVoice, to visually depict and narrate recovery stories. Aspirational figures conduct myth busting exercises and share their experiences treating PWLE. Outcomes among PCPs will include stigma knowledge, explicit and implicit attitudes, and mental healthcare competencies. To understand the feasibility, and acceptability of the intervention, qualitative interviews will be carried out with PWLE, family members, and aspirational figures, PhotoVoice trainers, mental health specialists co-leading the primary care trainings, and PCPs receiving mental health training. The sites will also generate evidence regarding feasibility, acceptability, recruitment, retention, fidelity, safety, and usefulness of the intervention to make further adaptations and modifications. The results will inform cross-cultural guidelines for collaboration with PWLE when conducting mental health training of primary healthcare workers. The results will be used to design future multi-site hybrid trials focusing on effectiveness and implementation.